Analisis Strategi Pemasaran Terhadap Tingkat Kepuasan Pelanggan Ojolali.Com - Liawatimena, S.; Johan, Johan; Selamat, Selamat (Journal the Winners: Economics, Business, Management, and Information System Journal, 2004)
The purposes of this research is to measure the customer demand in relation to the services of Ojolali.com. Therefore, it can be considered services that always met the customers demands. In this research, analysis to know the position of the Ojolali.comÂ  company and suitable strategy to conduct are also done. The results of this research gives a complete description on customer characteristic, buyer behaviour, the percentage of customer demand which is appropriate to level on Ojolali.com working performance, and the position of Ojolali.com on SWOT Matrix, and the suitable strategy, that is using opportunity to minimize the weakness.